Pathological Aspects of Haemonchosis in Goats and Sheeps - Riza Zainuddin Ahmad; Rida Tiffarent (Indonesian Center for Animal Research and Development, 2020)
Haemonchosis in sheep and goats has a high prevalence rate in several regions in Indonesia and causes economic losses. The purpose of this paper is to explain the clinical symptoms and pathological aspects of Haemonchus contortus infection so that knowledge is expected to help in controlling haemonchosis. Clinical symptoms of haemonchosis is characterised by decreased production, cachexia, and severe anaemia due to worms that sucking blood from the abomasal mucosa. In chronic infections the symptoms shows general oedema. Gross pathological findings are pale mucosa and carcass, hydrothorax, ascites, and haemorrhagic abomasum. Whereas histopathological features shows desquamation of villous abomasum, extensive hemorrhage of abomasal mucosa-submucosa, infiltration of large numbers of eosinophil and mononuclear cells, and cells undergoing degeneration and necrosis of internal organs. In general, the above exposure will show that haemonchosis usually associated with anaemia, cachexia, oedema, haemorrhage, infiltration of eosinophil and mononuclear cells in the abomasal mucosa.